A Deep Dive into the Emotional, Spiritual, and Socio-Religious Dimensions of Syair Soenoer - Yulia, Novi; Andoni, Yudhi (Faculty of Humanities, Andalas University, Padang, West Sumatra in cooperation with Kato Institute., 2025)
The emotional expression found within Syair Soenoer is not a simple sentiment but a profound and agonized representation of a soul caught in the crucible of a civilization-defining conflict. It articulates a deeply personal crisis that mirrors the larger schism tearing apart Minangkabau society in the early 19th century. The poem’s central figure is one who experiences a radical rupture with his past, his community, and his own inherited identity. This rupture is described through potent imagery of flight and exile, where the protagonist flees from the familiar landscapes of his youth— the